Technologies of Managing the Operating Assets - Kabitova, Yevgeniya Vladimirovna; Iudina, Svetlana Valentinovna (International journal of recent technology and engineering, 2019)
This study is based on the use of discriminant analysis techniques in order to individualize the analytical tools to assess the efficiency of managing the operating assets of economic agents. It has been determined that for the enterprises belonging to the Group of Companies, different integral indicators with different levels of discrimination are created while using identical discriminant variables, according to which the opposite conclusions can be drawn about the population belonging to a particular class with the same values for each subject. The developed empirical compartment functions prove the thesis of the erroneousness of universalization and generalization of conclusions when applying statistical methods. In other words, the need to identify problems at enterprises, their development potential, and the specifics of made managerial decisions remains an urgent task of analyzing financial and economic activities.